Psychosocial Variables Affecting the Behavior of Street Inhabitants in Five Panamanian Shelters Miguel A. Ca????les M (London Journal of Research In Humanities and Social Sciences, 2023)
To test these hypotheses, we propose to conduct a quantitative study, with a non- experimental, cross-sectional and correlational design. The objective is to analyze the relationship between psychosocial factors and the behavior of homeless people in Panama, using observation, a structured interview, the MEC and a mental examination protocol as instruments. The sample will be composed of 160 homeless people from the John Paul II Center in Panama. It is expected to find a correlation between psychosocial factors and behavior, which would support the null hypothesis and reject the alternative hypothesis.
Keywords: Gaussian curvature; surface of rotation; the Minding coil; Bianchi transformations.